Streamlining recruitment and selection processes to improve Company XYZ’s organizational effectiveness - Manuel, Justine R. (Animo Repository, 2022)
Recruitment and selection are HR practices that contribute to a company’s competitiveness. This action research addressed the lack of clear and consistent recruitment and selection processes in Company XYZ by streamlining those processes. Company XYZ belongs to the e-commerce industry and offers services related to in-house and acquired brands in various digital platforms. The collaborative team within HR Group used frameworks as guide which include Becker’s Strategic Architecture for HR, Recruitment Process Model, and Dual-Stage Model of the Recruitment Process. Interventions during Cycle 1 and Cycle 2 of this action research focused on developing a flowchart and process manual to help us create a streamlined recruitment and selection processes and incorporating a skill test to improve our screening process. Overall, these resulted in lessening hiring demands brought about role vacancies in Company XYZ and producing quality hires through a skill test we administered. This action research will benefit other small and medium enterprises and e-commerce enablers which require streamlining across their operations. Insights gained from this action research suggests a more holistic approach to human resource management.